Temporal Bone Osteoradionecrosis: An 18‐year, Single‐Institution Experience. (20th July 2021) - Lovin, Benjamin D.; Hernandez, Mike; Elms, Hunter; Choi, Jonathan S.; Lindquist, Nathan R.; Moreno, Amy C.; Nader, Marc‐Elie; Gidley, Paul W.
Abstract : Objectives/Hypothesis: To report the largest single‐institution review of temporal bone osteoradionecrosis (TBORN), and characterize the disease's natural history, prognostic factors, management, and outcomes. Study Design: Retrospective chart review. Methods: Retrospective review was conducted to identify patients with TBORN. Pertinent data were extracted. Descriptive statistics were used to summarize patient, tumor, and treatment characteristics. Multivariable analyses were conducted to explore associations between these characteristics and time to TBORN diagnosis and risk of developing diffuse disease. Results: TBORN was identified in 145 temporal bones from 128 patients. Mean age at diagnosis was 62 years, and mean time to diagnosis after radiotherapy was 10 years. Age greater than 50 years was associated with earlier diagnosis. According to the Ramsden criteria, 76% of TBs had localized and 24% had diffuse disease at initial diagnosis; 37% had diffuse disease at last follow‐up. On multivariable analysis, diabetes, three‐dimensional conformal radiotherapy (3D‐CRT), and periauricular skin malignancy were significant risk factors for developing diffuse disease. Localized disease was successfully managed with conservative measures, whereas surgery was often necessary for diffuse disease. When TBORN spread outside the mastoid or infratemporal fossa, conservative measures were always unsuccessful. Conclusions: TBORN occurs earlier in older patients. While diffuse disease is less common than localized disease, it occurs more frequently in patients with diabetes, history of 3D‐CRT, and periauricular skin malignancies. Conservative management is appropriate for localized disease, while surgery is often necessary for diffuse disease. The prognostic factors identified helped propose a TBORN staging system and treatment guidelines which may improve patient risk stratification and disease management. Level of Evidence: 4 Laryngoscope, 131:2578–2585, 2021